2017
DOI: 10.1007/s00253-017-8624-7
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic properties of β-N-acetylglucosaminidases

Abstract: β-N-Acetylglucosaminidases (GlcNAcases) hydrolyse N-acetylglucosamine-containing oligosaccharides and proteins. These enzymes produce N-acetylglucosamine (GlcNAc) and have a wide range of promising applications in the food, energy, and pharmaceutical industries, such as synergistic degradation of chitin with endo-chitinases and using GlcNAc to produce sialic acid, bioethanol, single-cell proteins, and pharmaceutical therapeutics. GlcNAcases also play an important role in the dynamic balance of cellular O-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 78 publications
6
39
0
Order By: Relevance
“…The O-GlcNAc eraser, OGA, was identified by Hart et al in 1994 and is mainly present in the cytosol [12,62]. OGA catalyses the removal of O-GlcNAc from proteins via a substrate-assisted mechanism, utilizing the acetamido group of the sugar moiety [63,64]. Thus, in addition to OGT, the regulation of OGA needs to be tightly controlled to prevent disease.…”
Section: Regulation Of O-glcnacylationmentioning
confidence: 99%
“…The O-GlcNAc eraser, OGA, was identified by Hart et al in 1994 and is mainly present in the cytosol [12,62]. OGA catalyses the removal of O-GlcNAc from proteins via a substrate-assisted mechanism, utilizing the acetamido group of the sugar moiety [63,64]. Thus, in addition to OGT, the regulation of OGA needs to be tightly controlled to prevent disease.…”
Section: Regulation Of O-glcnacylationmentioning
confidence: 99%
“…Although chitinases, that is, enzymes that catalyze the hydrolysis of chitin into its monomer, offer an opportunity for clean processing of chitin (Scheme ), their use is hindered by the poor solubility of chitin, which requires harsh pretreatment of the chitinous material, for example, with HCl to form a colloidal chitin suspension, or by using phosphoric acid to generate swollen chitin . Further, there is a need to improve chitinase activity and stability for biotechnological applications …”
Section: Introductionmentioning
confidence: 99%
“…[28] Further,t here is an eed to improve chitinase activity and stabilityf or biotechnological applications. [29,30] The challenges of using chitinasesf or the processing of chitinousb iomass are in contrast witht he natural ability of these Chitin is not only the most abundantn itrogen-containing biopolymer on the planet, but also ar enewable feedstock that is often treated as aw aste. Currentc hemical methods to break down chitin typicallye mployh arsh conditions, large volumes of solvent, and generate am ixture of products.…”
Section: Introductionmentioning
confidence: 99%
“…Producing high purity GlcNAc from chitinous biomass through chemical hydrolysis is, however, plagued by side reactions related to the harsh reagents needed to cleave the insoluble, unreactive polymer . Use of chitinolytic enzymes, or chitinases, in typical aqueous suspensions provides a more environment‐friendly depolymerization route, but is slow and still requires harsh pre‐treatment of the biomass …”
Section: Mechanoenzymatic Reactions Of Glycosyl Hydrolasesmentioning
confidence: 99%
“…[144,145] Producing high purity GlcNAc from chitinous biomass through chemicalh ydrolysis is, however,p lagued by side reactions related to the harsh reagents neededt oc leave the insoluble, unreactivep olymer. [146] Use of chitinolytic enzymes,o rc hitinases, [147] in typical aqueous suspensions provides am ore environment-friendly depolymerization route, but is slow and still requires harsh pre-treatment of the biomass. [148] Ar ecent study by Therien et al [149] demonstrated that chitinases are not only severalf old more efficient in the absence of bulk water,b ut are also more selective and generate ah ighly concentrated GlcNAcp roduct.…”
Section: Chitinase-catalyzed Depolymerization Of Chitin By Ragingmentioning
confidence: 99%